A Reduced‐Symmetry Heterobimetallic [PdPtL4]4+ Cage: Assembly, Guest Binding, and Stimulus‐Induced Switching. (30th April 2020) - Lisboa, Lynn S.; Findlay, James A.; Wright, L. James; Hartinger, Christian G.; Crowley, James D.
Abstract: A strategy is presented that enables the quantitative assembly of a heterobimetallic [PdPtL4 ] 4+ cage. The presence of two different metal ions (Pd II and Pt II ) with differing labilities enables the cage to be opened and closed selectively at one end upon treatment with suitable stimuli. Combining an inert Pt II tetrapyridylaldehyde complex with a suitably substituted pyridylamine and Pd II ions led to the assembly of the cage. 1 H and DOSY NMR spectroscopy and ESI mass spectrometry data were consistent with the quantitative formation of the cage, and the heterobimetallic structure was confirmed using single‐crystal X‐ray crystallography. The structure of the host–guest adduct with a 2, 6‐diaminoanthraquinone guest molecule was determined. Addition of N, N′‐dimethylaminopyridine (DMAP) resulted in the formation of the open‐cage [PtL4 ] 2+ compound and [Pd(DMAP)4 ] 2+ complex. This process could then be reversed, with the reformation of the cage, upon addition of p ‐toluenesulfonic acid (TsOH). Abstract : Open, sesame ! A method for the quantative assembly of the heterobimetallic cage, [PdPtL4 ] 4+, is described. The cage interacts with quinone guest molecules in a 1:1 fashion. The cage can be selectively and reversibly opened then re‐closed at the Pd II end by the sequential addition of base then acid. Guest molecules can be reversibly released/bound during this process.